(3bjGS JcdaI eNGWQ GdEFJeGf GdeUQaj aj GdHfhc GdJLGQjIs - (3eMeO eMehO YHO QHg(B, (3eMeOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI ddfTQ(B,s, 2000)
(3CgejI hCgOGa bjGS JcdaI eNGWQ GdEFJeGf aj GdHfhc GdJLGQjI(B-(3eNGWQ GdEFJeGf aj GdHfhc GdJLGQjI(B-(3bjGS JcdaI eNGWQ GdEFJeGf aj GdHfhc GdJLGQjI(B"(3fehPL eMGSHj ebJQM(B"(3OQGSI hJMdjd GdfJGFL(B"(3GdOQGSI GdJWHjbjI(B"-(3GdNdGUI hGdfJGFL hGdJhUjGJs
(3HHdjhZQGajG(B: (3U(B.201-211s
Keywords: (3GdEFJeGf, eNGWQs; (3GdHfhc JLGQjIs; (3GdeNGWQ GdeGdjIs; (3eMGSHI GdJcGdjas